THE ROLE OF AUDIO-VISUAL MEDIA IN TEACHING LEARNING PROCESS OF LISTENING COMPREHENSION AT THE NINTH GRADE OF MTS. AL-HUDA SUMBER NANGKA PAMEKASAN - Darrin Zuhri; A Fanani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2018)
The objectives of this study were to describe the kinds of audio-visual media used by the teacher in teaching learning process of listening comprehension at the ninth grade of MTs. Al-Huda Sumber Nangka Pamekasan, how the way to implement the audio-visual media in teaching learning process of listening comprehension at the ninth grade of MTs. Al-Huda Pamekasan, the advantages got by the teacher and students in teaching learning process of listening comprehension by using audio-visual media, and the ninth grade students’ response toward the use of audio-visual media in teaching learning process of listening comprehension. The population of this study was the ninth grade of MTs Al-Huda Sumber Nangka-Pamekasan, namely: IX-A and IX-B, the number of the ninth grade students is 51 students. The sample of this study is 51 students of the ninth grade and an English teacher. Here, researcher took the whole population as the sample because it was less than 100. And in this study, the researcher applied descriptive qualitative method. The location of this research was at MTs. Al-Huda Sumber Nangka Duko Timur Village-Larangan-Pamekasan-East Java. This research had done four times. The first, it was done on July 24, 2008, the second, on July 28, 2008, the third, on August 4, 2008, and the fourth, on August 11, 2008. The result of the study showed that audio-visual media was used to motivate and attract students’ attention. Audio-visual media also functioned to activate students, save time, reduce verbalism, and make the explanation clearer and the class more alive. When the teacher used audio-visual media, the teaching learning process became more effective and efficient because it could be helpful for him and his students. All students (100 %) agreed that their teacher used audio-visual media and they liked it. Most of them (94,1 %) agreed that if their teacher used audio-visual media, his explanation become more understandable, 50 respondents (98 %) agreed that if their teacher used audio-visual media, the lesson become more interesting, and 46 respondents (90,2 %) agreed that they became more active. The audio-visual media has an important role to make the teaching learning process of listening comprehension more effective and efficient because it can help the teacher and students in understanding material.